2006
DOI: 10.1080/09542299.2006.11073749
|View full text |Cite
|
Sign up to set email alerts
|

Mixed ligand complexes of toxic metal ions with L-glutamic acid and L-methionine in urea-water mixtures

Abstract: Speciation of mixed ligand complexes of Pb(II), Cd(II) and Hg(II) with L-glutamic acid and L-methionine was studied in varying amounts (0.0 -36.83%wyv) of urea in aqueous solutions maintaining an ionic strength of 0.16 mol dm À 3 (NaNO 3 ) at 303 K. Titrations were carried out in the presence of different relative concentrations (M : L : X ¼ 1 : 2 : 2, 1 : 2 : 4, 1 : 4 : 2) of metal (M) to L-glutamic acid (L) to L-methionine (X) with sodium hydroxide. Stability constants of ternary complexes were refined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…2 and 3, respectively. The two different ligands have mutually the same degree of in uence in the formation of mixed ligand complex [14,15,34,43].…”
Section: Prediction Of Extra Stability Of the Mixed Ligand Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3, respectively. The two different ligands have mutually the same degree of in uence in the formation of mixed ligand complex [14,15,34,43].…”
Section: Prediction Of Extra Stability Of the Mixed Ligand Complexesmentioning
confidence: 99%
“…Mononuclear binary complexes involving interaction of single metal with one ligand and mixed ligand complexes that contain more than one ligand have been studied for long time [9,10]. The stabilities of the synthesized complexes are a direct function of many factors such as: dielectric constants [11][12][13][14][15][16], stacking interactions between ligands, and metal-ligands [13][14][15][16][17][18], and electrostatic and non-electrostatic interactions [7,9,[11][12][13][14][15][16]. Literature reports indicated that most of these factors were mainly dependent on the composition of organic solvents, which could alter the dielectric constant of the medium and solvating power of the solvents [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent compounds involved in Cd tolerance are metalbinding peptides and phytochelatins (PCs). The former are cysteine-rich, found mostly in plants, capable of neutralizing toxic Cd ions and contain glutamic acid in a δ-bond, allowing them to form thiolate bonds with Cd ions (Rao et al, 2006) and thus protect plant cells from damage. On the other hand, PCs are important not only due to their metal-binding capacity, but also because they transport the bound metal ions from the cytoplasm into the vacuoles, where they can be stored as nontoxic form, bound to organic acid ligands (Brunetti et al, 2011;.…”
Section: Sa and Complexation Of CD By Peptidesmentioning
confidence: 99%